Aesthetic Applications of Intense Pulsed Light - Fodor, Lucian; Ullman, Yehuda; Elman, Monica; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
There has been a steady increase in aesthetic procedures performed over the past few years, and this increase has also been matched by the desire for a minimally invasive procedure with long-lasting results. Intense pulsed light (IPL) technology has proved to be of real benefit in satisfying these patient demands, the main advantages of this noninvasive technology being the minimal recovery downtime, fast and easy performance, and long-term improvement. Aesthetic Applications of Intense Pulsed Light is a thorough resource for physicians dealing with IPL cosmetic procedures. The goal of the book is to help clinicians, residents, fellows and other medical professionals understand IPL and perform treatments for various cutaneous conditions. The topics covered include the main cosmetic applications of IPL, anatomy, safety, practical issues, patient selection, the various treatment options and potential complications, while each chapter has been designed to assist in the clinical application of IPL and ends with key points that emphasize the most important take-home messages to achieve the best results. It is created to provide in-depth analysis and to reveal the practical approach, making this text the ideal reference and a teaching instrument for both beginner and experienced physician in the field of aesthetic medicine.
1. Skin anatomy -- 2. Light-tissue interaction -- 3. IPL safety and legal issues -- 4. Patient selection -- 5. Skin rejuvenation -- 6. Hair removal -- 7. Vascular lesions treatment -- 8. Complications.
Keywords: Medicine; Dermatology; Surgery; Medicine & Public Health; Dermatology; Surgery; Plastic Surgery